Restrição alimentar na terminação de bovinos alimentados sem volumoso - Domingues, Camille Carijo (2018)
The objective of the research was to investigate the food control in cattle finishing phase, without forage diet at levels of 7.5 and 15% of consumption restriction of ad libitum cattle, and its effects on performance, behavior and blood constituents. The experiment was conducted at the Laboratório de Bovinocultura de Corte of the Department of Zootechnics the Federal University of Santa Maria (UFSM). Were used 27 cattle with Charolais x Nellore predominance, with initial age and average weight of 27 months and 350 kg of live weight respectively. The treatments were: Diet without forage with feed ad libitum (Control Group); Diet without forage with restriction 7.5% of ad libitum intake; Diet without forage restriction 15% of ad libitum intake. The experimental design was completely randomized, with nine replicates, three treatments and three periods, the experimental unit being the cattle. The intake of dry matter, crude protein, total digestible nutrients, neutral detergent fiber, when expressed as a percentage of body weight and metabolic weight were higher for steers fed ad libitum not influencing the performance. Cattle from the control group spent more time on total chewing and feeding, than the cattle from the 15% restriction, while the cattle from the 7.5% restriction presented intermediate behavior. The leisure time was inversely proportional to the variables mentioned above. The cattle of the control and restriction group 7.5% presented superiority for number of daily meals and frequency of water intake, while cattle of the restriction group 15% presented inferior behavior. The concentration of triglycerides in the blood was higher for the control group (P> 0.05). The use of feed restriction in beef cattle does not affect animal performance, however, it decreases consumption as a percentage of live weight and metabolic weight unit, as well as lower feed intake, number of daily meals, total chewing time and frequency of water, presenting lower levels of triglycerides in the blood when compared to cattle fed ad libitum.